Percorsi progettuali di un laboratorio didattico. Hooke Park: un parco, un bosco e una scuola di architettura. - Elena Barthel (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
Defining Hooke Park is not easy: is it a park, a woodland or, as it says on the front gate, a ‘School of Architecture’? Which is the right hierachy? Which function has priority? The public space, the woodland or the university? The answer appears to be that Hooke Park is unique and represents a great opportunity because of its many functions. Every day the citizens of Hooke village walk through the park, perhaps even horse riding or cycling, together with kids playing, hunters hunting, and the Architectural Association students experimenting with contemporary architecture. This is Hooke Park: 150 hectares of woodland owned by one of the most renowned schools of architecture in Europe. How better to define it than: “a rare opportunity?”. This essay tells the story of the work of Diploma 9, a design studio looking at Hooke Park Strategy Plan, searching for a durable and self sustaining future.